The role of ESAT-6 in tuberculosis immunopathology - Passos, Beatriz B. S.; Araújo-Pereira, Mariana; Vinhaes, Caian L.; Amaral, Eduardo P.; Andrade, Bruno B. (Frontiers in Immunology, 2024)
Despite major global efforts to eliminate tuberculosis, which is caused by Mycobacterium tuberculosis (Mtb), this disease remains as a major plague of humanity. Several factors associated with the host and Mtb interaction favor the infection establishment and/or determine disease progression. The Early Secreted Antigenic Target 6 kDa (ESAT-6) is one of the most important and well-studied mycobacterial virulence factors. This molecule has been described to play an important role in the development of tuberculosis-associated pathology by subverting crucial components of the host immune responses. This review highlights the main effector mechanisms by which ESAT-6 modulates the immune system, directly impacting cell fate and disease progression.